Keberlanjutan Dana Simpan Pinjam Perempuan Eks Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan dalam Peningkatan Ekonomi Masyarakat Desa - Dimas Kurnianto; Badaruddin Badaruddin; Humaizi Humaizi (PERSPEKTIF, 2021)
This study aims to examine the sustainability of the ex-PNPM Independent Rural Women's Savings and Loan (SPP) in improving the economy of the Sei Rampah sub-district community. Methodologically, this research uses qualitative methods with a descriptive approach. Data collection techniques are interviews, focused group discussions (FGD), and observation of the processes and results of SPP activities in Sei Rampah sub-district and collect secondary data in the form of literature studies on literature, documents, scientific writings and similar research studies related to the problem research. Data analysis was performed by reducing data, presenting data and drawing conclusions. The result of this research is that the sustainability of SPP Ex PNPM MPd funds is still continuing and developing very well with significant benefits for improving the economy of the poor. The institution that manages the SPP ex PNPM MPd fund is the BKAD which is reorganized through inter-village deliberations which are determined as joint decisions of the village head. The BKAD institutional status is still ad hoc and has not been transformed into a legal entity. The Ex-PNPM MPD Women's Savings and Loans Program (SPP) has not joined into a business unit within the Joint BUMDesa so that business development has not been maximized and utilization and loans have not been evenly distributed to all poor households.